Determinar las concentraciones de sulfuro y arsénico en el río Amarillo en el sector El Pache del cantón Portovelo durante los meses de agosto a noviembre del 2008 - Murgueitio Quintana, Zhirahy X. (2009)
The present investigation development in the province of El Oro of Ecuador and i son the determination about the levels of arsenic and sulfides in waters the Amarillo river, river that are seen strongly affected by auriferous the mining activity, whose plants of benefit are based in the creeks of the same one during several decades and have caused the deterioration of the biotic conditions, as well as multiple damages in the surrounding population.